Efektivitas Model Pembelajaran Realistik Matematika pada Materi Pecahan SMA N 1 Gerung - Indah Permata Sari; Yolanda Kurnia (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study aims to examine the effectiveness of implementing the Realistic Mathematics Education (RME) model in improving students’ understanding of fractions at SMA Negeri 1 Gerung. The background of this research is based on the low level of students’ understanding of fraction concepts, which are often abstract and difficult to comprehend through conventional teaching approaches. RME was selected as a strategic alternative because it emphasizes the connection between mathematical concepts and students’ real-life experiences, making learning more contextual and meaningful. The research method used was a quasi-experimental design with a pretest-posttest control group format. The sample consisted of two classes: an experimental class that applied the RME model and a control class that used conventional teaching methods. The research instruments included a conceptual understanding test and an observation sheet to assess students’ learning activities. The results of data analysis indicated a significant difference between the posttest scores of students in the experimental class and those in the control class, with a higher average improvement observed in the class that implemented RME. In addition, students demonstrated greater engagement and enthusiasm during the learning process. These findings suggest that RME is effective in enhancing students’ understanding of fraction concepts and in promoting active participation. Therefore, it is recommended that mathematics teachers consider implementing RME as an alternative approach in teaching fractions at the senior high school level.